2017
DOI: 10.1108/ijqss-10-2016-0074
|View full text |Cite
|
Sign up to set email alerts
|

The effect of role stress, job satisfaction, self-efficacy and nurses’ adaptability on service quality in public hospitals of Wajo

Abstract: Purpose This study aimed to determine the effect of role conflict and role ambiguity on job satisfaction, self-efficacy and nurses’ adaptability and improvement in service quality by analysis of quality function deployment. Design/methodology/approach This study used a cross-sectional study design. The research sample of 115 nurses and 299 patients was obtained through the use of probability sampling techniques. Data were statistically analyzed using Spearman’s test to see the correlation between independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 8 publications
1
21
0
1
Order By: Relevance
“… Kim et al (2009) conducted a study on hotel employees and found that role conflict and role ambiguity are two important factors that affect job satisfaction and turnover intention of employees. A study based on a group of nurses showed that high role stress experienced by individuals leads to anxiety and dissatisfaction ( Kadir et al, 2017 ). According to the conservation of resources theory (COR), role stress is the process of burning out internal resources that can lead to a change in the attitude of work of individuals, the occurrence of psychological withdrawal, and poor well-being when no effective resource supplementation is available.…”
Section: Literature Reviewmentioning
confidence: 99%
“… Kim et al (2009) conducted a study on hotel employees and found that role conflict and role ambiguity are two important factors that affect job satisfaction and turnover intention of employees. A study based on a group of nurses showed that high role stress experienced by individuals leads to anxiety and dissatisfaction ( Kadir et al, 2017 ). According to the conservation of resources theory (COR), role stress is the process of burning out internal resources that can lead to a change in the attitude of work of individuals, the occurrence of psychological withdrawal, and poor well-being when no effective resource supplementation is available.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most job satisfaction approaches are based on motivational theories developed by Herzberg, Maslow and Vroom [11]. Research indicates that nurses' job satisfaction has a significant impact on their quality of service [12]. Nurses job satisfaction has an effect on duties that are focused more on patients and their family than on administrative duties.…”
Section: Introductionmentioning
confidence: 99%
“…Providing services to patients on the basis of their expectations and needs is a necessary and important step in offering high-quality services for the success of an organization to remain competitive in the market (Aghamolaei et al, 2014). Hospitals have a very strategic role in accelerating the enhancement of public health (Kadir et al, 2017). The demand for better service quality is rising due to the increased aspiration level of customers with an increase in their per capita income (Singh and Prasher, 2019).…”
Section: Introductionmentioning
confidence: 99%